Franchisingový koncept pro rozvoj autoservisu - Konečný, Lukáš (Vysoké učení technické v Brně. Fakulta podnikatelská, 2009)
Diplomová práce se zabývá možností expanze a rozšíření stávajícího podnikání vybudováním franchisingového řetězce. V České republice je vytvoření vlastního franchisingového konceptu doposud vzácnosti, protože tato možnost expanze není českým podnikatelům dostatečně známá. Výstupem práce bude navržení franchisingového konceptu pro společnost AUTO HORÁK. Navrhovaný koncept je koncipován tak, aby umožnil společnosti základ pro její expanzi.

Master's thesis deals with the possibility of expansion and the expansion of existing business with franchising chain.The creation of own franchising concept is still very scarcity in The Czech republic, because the possibility of expansion is not sufficiently well known to Czech entrepreneurs. The outcome of the work will be proposing the concept of franchising for the company AUTO HORÁK. The concept is designed to allow a basis for its expansion.
Franchising Concept for Develoment of Car Repair Service
Keywords: Franchising; franchisor; franchisant; franchisingová smlouva; franchisingový koncept; manuál; Franchising; franchisor; franchisee; franchising agreement; franchising concept; manual